Sadness at the Rainbow: Unraveling the Unheard Sentiments of Non-Binary Students - Caluya, Eisen Jeremy; Realin, Nina Louchel; Sabalburo, Lanz Enrico; Salazar, Karylle Anne; Villostas, Chynelle; Galdonez, Dominic Patric G. (Future Science / FSH-PH Publications, 2023)
The number of individuals identifying as non-binary or genderqueer has significantly increased over time. This group experiences their gender identity as neither entirely male nor exclusively female; instead, they perceive it as a combination or a complete absence of binary gender identification that may evolve or remain consistent over time. Nevertheless, there is a limited amount of research focusing on the experiences of non-binary students, leading to common misunderstandings within their community. Consequently, this study sought to delve into the physical, mental, interpersonal, emotional, and spiritual experiences of non-binary students. To analyze the collected data, a qualitative approach, specifically a narrative research design, was employed. Three students from the Philippine Science High School - Ilocos Region Campus were chosen through snowball sampling to share their personal experiences as non-binary students. Based on the gathered information, it can be concluded that non-binary students in the PSHS-IRC community undergo a range of experiences that significantly affect their physical, mental, interpersonal, emotional, and spiritual well-being. It was observed that they struggle to form a positive self-image due to their dissatisfaction with their physical appearance. Additionally, their body dysmorphia, stemming from a dislike for their bodies perceived as too masculine or feminine, negatively impacts their mental health. Moreover, homophobia continues to disrupt their interpersonal relationships, as they often endure physical, mental, emotional, and spiritual abuse. Nonetheless, they still have support networks that provide ongoing assistance. Lastly, the results also indicate that their faith in Christianity has waned due to relentless verbal attacks from conservative individuals.